Firm Age, Investment Opportunities, and Job Creation - ADELINO, MANUEL; MA, SONG; ROBINSON, DAVID (Journal of Finance, 2017)
ABSTRACT New firms are an important source of job creation, but the underlying economic mechanisms for why this is so are not well understood. Using an identification strategy that links shocks to local income to job creation in the nontradable sector, we ask whether job creation arises more through new firm creation or through the expansion of existing firms. We find that new firms account for the bulk of net employment creation in response to local investment opportunities. We also find significant gross job creation and destruction by existing firms, suggesting that positive local shocks accelerate churn.